TEACHING ENGLISH AS A SECOND LANGUAGE - Shakhlo Farmonova (American Journals Publishing, 2023)
This article discusses innovative ways to teach English as a second language to school students. Nowadays, language learning is one of the most urgent issues, the article discusses the methods of teaching English to schoolchildren in various new methods, including teaching with the help of games.
Keywords: Teaching methodology, foreign languages, international communication, activities, English teachers.